(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
The evolution of library and information services has seen significant transformations, with each generation responding to the changing needs of users and technological advancements. This paper explores the emergence of the fourth generation of library and information services, which goes beyond traditional boundaries by embracing digital technologies, open access, and user-centric models. It examines how libraries are redefining their roles in an increasingly interconnected world, focusing on the integration of artificial intelligence, cloud computing, and data management systems to enhance user experience and service delivery. The study highlights the shift from physical to virtual spaces, the democratization of information, and the increasing emphasis on personalized and accessible services. By analyzing current trends and challenges, this paper provides insights into how libraries and information centers are adapting to serve the evolving needs of diverse user communities in the digital age.